Sustainable competitive advantage in maternal and child health institutions: A dynamic capability approach - Yuan, H.; Ferreira, F. (Annals of Operations Research, 2025)
China’s government has always attached great importance to protecting women and children’s rights and has made a consistent effort to promote their all-round health. The on-going medical reforms in the country have resulted in a falling birth rate and rising demand for increasingly diversified, multi-level healthcare services. Maternal and child health (MCH) institutions have had to implement more extensive changes and deal with greater challenges in order to survive and develop. MCH organizations thus need to find ways to improve their competitiveness. This study integrates qualitative and quantitative business analytics methods by conducting empirical research using varied techniques, namely the Delphi method and analytic hierarchy process (AHP). A panel of experts were consulted in three rounds of surveys, and the results were processed with AHP in order to develop an evaluation indicator model of MCH institutions’ competitive advantages. Ten hospitals were selected to verify the model’s applicability. Sensitivity analysis confirmed that the model has good stability. The proposed model highlights that human resources have the greatest weight as a determinant of competitive advantage. The findings, therefore, concentrate on people as the core resource, suggesting that MCH institutions can acquire and maintain competitive advantages based on three dimensions: department leader development, improved scientific research capacity, and a more flexible hospital culture.